2007
DOI: 10.1093/ajcn/86.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate nutrition and metabolism

Abstract: The persistence of an epidemic of obesity and type 2 diabetes suggests that new nutritional strategies are needed if the epidemic is to be overcome. A promising nutritional approach suggested by this thematic review is carbohydrate restriction. Recent studies show that, under conditions of carbohydrate restriction, fuel sources shift from glucose and fatty acids to fatty acids and ketones, and that ad libitum-fed carbohydrate-restricted diets lead to appetite reduction, weight loss, and improvement in surrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
216
3
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(254 citation statements)
references
References 85 publications
5
216
3
15
Order By: Relevance
“…Increased ketogenesis, and therefore insulin resistance, may be expected to increase during carbohydraterestricted diets. 24 However, ketogenesis was not evident in the pilot trial. Participants were asked to test for blood ketones at least weekly and if their blood glucose levels were higher than 15 mmol/L.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Increased ketogenesis, and therefore insulin resistance, may be expected to increase during carbohydraterestricted diets. 24 However, ketogenesis was not evident in the pilot trial. Participants were asked to test for blood ketones at least weekly and if their blood glucose levels were higher than 15 mmol/L.…”
Section: Discussionmentioning
confidence: 86%
“…The reported mealtime insulin resistance could have been caused by a negative effect on insulin sensitivity due to an increase in saturated fat 24 in the LCC group's diet, but the main study showed there was no increase. Insulin dose requirements may have been partially affected by inaccurate carbohydrate counting, as has been reported elsewhere; 25 another possibility is that in people with a limited carbohydrate intake, gluconeogenesis becomes such an important source of glucose that it becomes necessary to also calculate the protein content of a meal and use an insulin:carbohydrate and protein ratio.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies comparing the effects of CRD and conventional diets without resistance training reported significant decreases in fat-free mass in both interventions (from -1.4 to -3.2 kg, representing up to 32% of total body mass reduction) 2,6,10,24,25 . However, despite the short duration of the present intervention, CRD associated to resistance training seemed to prevent fat-free mass loss.…”
Section: Discussionmentioning
confidence: 90%
“…The mean carbohydrate intake among the CRD group was 83±43 g at week 8, and all subjects ingested amounts below the upper limit that characterizes a CRD (<150 g daily) 2 . In the CRD group, the ingestion of carbohydrate was below the recommendations of IOM 13 , while protein and fat intakes were above the upper limits.…”
Section: Tc/hdl-c Ratiomentioning
confidence: 93%
See 1 more Smart Citation